“Un Paso Atrás, Dos Adelante” (One Step Back, Two Steps Forward): Reporting the Experiences of Spanish-Speaking Latin Americans in Canadian Workplaces - Merchán Tamayo, Jully Paola (Université d'Ottawa / University of Ottawa, 2022)
The linguistic landscape of Canadian workplaces is becoming more diverse as organizations employ individuals who come from various countries and speak different native languages. As language is an important marker of identity and group membership, language-based identities are powerful in shaping workplace experiences. Guided by both the ethnolinguistic identity theory (ELIT: Giles et al., 1977; Giles & Johnson, 1987) and communication accommodation theory (CAT: e.g., Dragojevic et al., 2016; Gallois et al., 2005; Giles & Ogay, 2006), this study explores the experiences of Spanish-speaking Latin Americans working in the Canadian National Capital Region in relation to their linguistic identities, coping strategies, and intergroup interactions. A thematic analysis of 24 semi-structured interviews shows that participants experience a dynamic shift in their identity in which they move between feelings of self-doubt and a sense of confidence and comfort in their workplaces. This shift occurs as they navigate the cognitive and emotional experiences of working in a nonnative language. Factors that influence this identity shift include social comparisons, positive implications associated with their native linguistic identity, negative evaluations, and empathy in the workplace. This study also provides a detailed description of the intrapersonal, interpersonal, and interactional coping strategies that participants enact to navigate their workplaces. In terms of intergroup interactions, the participant’s experiences, their evaluations, and reactions to accommodative or nonaccommodative behaviours from native speaking peers in their workplaces are explored. The final pages of this study include some recommendations for human resource practitioners.
Keywords: Language diversity in the workplace; Linguistic identity; Phenomenological study; Ethnolinguistic identity theory; Communication accommodation theory; Spanish-speaking Latin Americans in Canadian workplaces